Decomposição de forrageiras sob doses de glyphosate e níveis de sombreamento - Matheus Caldeira Brant (2015)
Knowledge of straw degradation dynamics of forage plants for ground cover is essential to keep the benefits provided by these plants in no-till system. In integrated systems where there is no soil disturbance, maintaining mulch can be influenced by the management adopted to form it, by the species used and by the environment. In the present study we sought to evaluate the influence of the culture environment and the glyphosate doses used for the drying of both forages on the formation of straw, its decomposition and in the soil microbial activity. Two experiments were conducted, one for Piatã grass (Urochloa brizantha cv. Piatã) and one for Tanzania grass (Megathyrsus maximus cv. Tanzania). The experiments were conducted in randomized blocks, in factorial scheme 2 x 6, with four repetitions for each forage. Factor I was represented by two cultivation environments (full sun and under 50% of shade) and factor II for six doses of glyphosate (0, 360, 720, 1080, 1440 and 1800 g ha-1) used in drying fodder. The productivity of dry mass of Piatã grass was influenced by the presence of shading. Plants cultivated in the shade were more susceptible to herbicide doses, however, influences of herbicide doses in the straw degradation were not observed; the shading reduced this variable for both forages. The application of herbicide doses altered the release of accumulated CO2 in the soil samples, except the Tanzania grass samples grown in the shade. The Piatã grass and Tanzania grass cultivation under 50% of shade allows reduction of glyphosate doses to dry, being the shadow capable to slow the degradation of the two forages straw. In the shaded environment there is more microbial biomass breathing.